Thinking and Learning Style - Yahaya, Azizi (2006)
The mind has three basic functions: thinking, feeling, and wanting. The process of thinking creates meaning or making sense of the events of our lives thereby . The process of feeling monitors those meanings or evaluating how positive and negative the events of our lives are, given the meaning we are ascribing to them. The process of wanting drives us to act in keeping with our definitions of what is desirable and possible. What is more, there is an intimate interrelation between thinking, feeling and wanting. When for example, we THINK we are being threatened, we FEEL fear, and we inevitably WANT to flee from or attack that which we think is threatening us. When students THINK a subject they are required to study has no relationship to their lives and values, they FEEL bored by instruction in it, and it develop a negative MOTIVATION with respect to it. The article discuss about various types of thinking skills which could be implemented in the teaching and learning process. Teaching thinking skills does have a great deal to offer but it will be effective only if it excites teachers who are skilled enough to work in this way. Instruction that fails to address the affective side of studentsâ€™ lives can eventually turn students into inveterate â€œenemiesâ€? of education.